Increasing Access to Acceptable and Affordable Gluten-Free Baked Goods - April Litchford; Karin Allen; Cindy Jenkins; Eva Timothy; Paige Wray (Journal of Human Sciences and Extension)
Transitioning to a gluten-free (GF) diet can be difficult due to limited reliable recipes to produce baked goods at home and poor quality of commercially available baked goods. This study tested basic recipes capable of creating acceptable GF baked products at home using commercially available GF flour blends. Recipes for a drop cookie, rolled cookie, bread, and pizza crust were tested and altered during this research to produce reliable recipes for GF baked goods. To assess the acceptability of these GF baked goods, products were tested for springiness, moisture content, hardness, height, spread, taste, appearance, and texture during in-lab testing and consumer in-home testing. Results suggest that the specific GF flour blend used changed the quality and acceptability of the products tested. Flour blends that contain higher amounts of starch by ingredient weight tend to produce more acceptable bread and pizza crust, while flour blends with less starch produced more acceptable drop and rolled cookies.